Transforming dryland forests and agrosilvopastoral systems training course - Haddad, Fidaa; Louhaichi, Mounir; Flintan, Fiona (Food and Agriculture Organization of the United Nations, 2023)
Training material's that belong to the Transforming dryland forests and agrosilvopastoral systems course that seeks to build the competencies needed for program and project managers, field practitioners and policy makers to apply a transformational sustainability approach to decision-making in the management of dryland forests and agrosilvopastoral production systems.